Optimization of Artificial Insemination in Buffalo through Modification of Estrus Synchronization Techniques Based on hCG (Human Chorionic Gonadotropin) - Rahma, Nadia; Ananta, Dwi (Jurnal Tropicalanimal, 2025)
Buffalo is one of the livestock species that play a crucial role in providing economically valuable products, such as meat, milk, and by-products. However, the development of buffalo farming in Indonesia over the past few years has not shown significant progress. One indication of this is the declining buffalo population across various regions. A major challenge in buffalo farming development is the occurrence of silent heat, which makes it difficult for farmers or inseminators to detect estrus. As a result, the implementation of artificial insemination (AI) is often suboptimal, leading to low conception rates in buffalo. One solution to this issue is the application of estrus synchronization techniques through the manipulation of reproductive hormones. This study aims to evaluate the effectiveness of hormone based estrus synchronization methods, particularly the use of hCG, in improving estrus intensity and conception rates in buffalo. The analyzed methods involve various hormonal protocols, including PGF2α, GnRH, PMSG, and hCG, based on relevant literature data. Using a literature review approach, data on estrus synchronization techniques were collected and developed into a scientific work with practical benefits.The findings of this study are expected to serve as a reference for farmers and inseminators to enhance the success of AI in buffalo through the application of more effective estrus synchronization methods. Keywords: hCG, estrus synchronization, silent heat, artificial insemination